Preliminary Evidence of Pre-Attentive Distinctions of Frequency-Modulated Tones that Convey Affect - Leitman, David I.; Sehatpour, Pejman; Garidis, Christina; Gomez-Ramirez, Manuel; Javitt, Daniel C. (Frontiers in Human Neuroscience, 2011)
Recognizing emotion is an evolutionary imperative. An early stage of auditory scene analysis involves the perceptual grouping of acoustic features, which can be based on both temporal coincidence and spectral features such as perceived pitch. Perceived pitch, or fundamental frequency (F0), is an especially salient cue for differentiating affective intent through speech intonation (prosody). We hypothesized that: 1) simple frequency modulated (FM) tone abstractions, based on the parameters of actual prosodic stimuli, would be reliably classified as representing differing emotional categories; and 2) that such differences would yield significant mismatch negativities (MMNs) - an index of preattentive deviance detection within the auditory environment. We constructed a set of FM tones that approximated the F0 mean and variation of reliably-recognized happy and neutral prosodic stimuli. These stimuli were presented to 13 subjects using a passive listening oddball paradigm. We additionally included stimuli with no frequency modulation (FM) and FM tones with identical carrier frequencies but differing modulation depths as control conditions. Following electrophysiological recording, subjects were asked to identify the sounds they heard as happy, sad, angry or neutral. We observed that FM tones abstracted from happy and no expression speech stimuli elicited MMNs. Post-hoc behavioral testing revealed that subjects reliably identified the FM tones in a consistent manner. Finally, we also observed that FM tones and no-FM tones elicited equivalent MMNs. MMNs to FM tones that differentiate affect suggests that these abstractions may be sufficient to characterize prosodic distinctions, and that these distinctions can be represented in pre-attentive auditory sensory memory.